STRATEGI MENINGKATKAN VOLUME PENJUALAN KRIPIK TEMPE DI MASA PANDEMI PADA HOME INDUSTRY SUMBER AGUNG, PETORAN, JEBRES, SURAKARTA - Marjam Desma; Lamidi (Universitas katolik Musi Charitas, 2021)
This community activity takes the object of the Sumber Agung home industry in Petoran, Jebres, Surakarta. The purpose of the activity is to provide training and counseling to Sumber Agung home industry managers in order to be able to adapt to changes in information technology, in an effort to manage and develop their business, and to help provide solutions to overcome problems faced, especially in the aspect of product marketing, among others: 1) during the covid 19 pandemic the sales of tempe chips experienced a very significant decline, around 50%, 2) the tempe slicing process is only done manually, even though under normal conditions it can consume 70 kg of soybean raw material/day, as a result it is inefficient in production, 3) the owner does not understand the importance of branding and packing. The method of implementing this activity is by providing assistance in the form of training and counseling at the Sumber Agung home industry. Technically, by holding training on the use of social media (whatsapp, facebook and instagram) and counseling on the importance of understanding branding and packing. The results of this mentoring activity were Facebook which was used by